Upaya Meningkatkan Kemampuan Numerasi Anak dalam Menulis Angka 8 melalui Media Vituleka - Suryantika, Renita; Widayati, Sri; Maulidiyah, Eka Cahya; Hasibuan, Rachma; Khumairoh, Lulu (Universitas PGRI Madiun, 2024)
The learning strategies and media used by educators will influence the success of achieving learning objectives. The use of appropriate media that suits the character of early childhood can support the achievement of learning goals effectively. Good numeracy skills at an early age are a strong foundation for further mathematics learning in the future. This research is based on children's ability to write the number eight (number 8) which is still imperfect. In general, children make the number eight by stacking circles from bottom to top. The aim of this research is to improve the numeracy skills of special children in writing the number 8. This classroom action research was carried out in group A at UNESA Labschool 1 Kindergarten. This classroom action research uses the Kemmis and Mc.Taggart method with two cycles. Each cycle includes planning, implementation, observation and reflection. This research uses video tutorials and children's worksheets (Vituleka). The subjects of this research were 18 group A students. In cycle I, students' numeracy ability in writing the number 8 was 50%. In cycle II, numeracy ability in writing the number 8 became 83.3%, an increase of 33.3% from the previous cycle. Based on research data, Vituleka media can improve students' ability to write the number 8.